Ban this book : a novel - Gratz, Alan, 1972- (Starscape, 2017)
When her favorite book in the school library is challenged by a well-meaning parent, Amy Anne and her friends start a secret banned books locker library, using ridiculous reasons to ban every book in the library to make a point.